INCIDENCE AND CLINICAL MANIFESTATIONS OF CONCUSIONS IN ADOLESCENT AND PRE-ADOLESCENT ATHLETES PRACTICING OLYMPIC SPORTS - Lopes Amorim, Gabriel; Assoni Bilibio, Sarah; Pflug Comparsi, Eduardo; Albuquerque Drummond, Felix; Petkowicz, Rosemary (Health and Society, 2023)
Background: Concussion is a frequent and sometimes severe complication of sport activity. The incidence in the USA is estimated at 538/100.000 person/year, while in Brazil there is no published estimate at that regard. The aim of our study was to evaluate the concussion incidence rate in adolescents and preadolescents athletes who practice different types of Olympic sports. Methods: This is a cross-sectional, retrospective study, which included volleyball, basketball, artistic gymnastics and judo adolescents (15-19 years old) and preadolescent (11-15 years old) athletes. An on line survey was sent to them by their coaches, and they were free to answer or not the questions. The central question was if they have had Traumatic Brain Injury/concussion in the last 12 months. If the answer was yes, then they had to respond to a questionnaire with several additional questions related to this concussion. Results: 66 athletes answered the survey; 23 out of 66 reported a concussion in the last 12 months. The overall incidence of concussion was 34.8%. The incidence per type of sport was 31,5% for volleyball, 20% for basketball, 57,1% for judo and 66,6% for artistic gymnastic. Those differences were not statistically significant, although there was a clear trend indicating the risk is higher for gymnastic and judo. There was no difference regarding the incidence according to gender or age distribution (adolescent versus preadolescents). The most frequent post-concussion symptoms were headache/migraine (73.9%), head pressure (26.1%), dizziness (13%), neck pain (13%) and changes in balance (13%). 12 out of the 23 (52.2%) athletes reporting a concussion had two or more symptoms (up to 8 symptoms). Conclusion: Our study showed that the incidence rate of sport concussions in our country is very high, at least in the universe of adolescent and preadolescent athletes. To our knowledge, this is the first report of concussion incidence in Brazil. It indicates that educational and medical measures should be employed as soon as possible, possibly under the lead of sport medicine specialists, in order to prevent or to deal with this complication in a standardized way.